Pengaruh Pemberian Ivermectin Terhadap Perubahan Sel Darah Putih pada Kambing Kacang yang Dipelihara Secara Intensif - Christvando Rendi Leba Tagu Bore; Frans Umbu Datta; Nemay Anggadewi Ndaong; Yustinus Oswin Primajuni Wuhan (JURNAL KAJIAN VETERINER, 2025)
This study aims to determine the effect of Ivermectin on the differential picture of white blood cells of pea goats before and after endoparasite treatment in a semi-intensive rearing system. The study used 11 pea goats placed in individual pens with a platform and fed with KGP 709 concentrate. Ivermectin was given at a dose of 2.5 ml/head. Tools used included a microscope, EDTA tube, syringe, centrifuge, glass slide and cover, and dropper pipette. Parameters observed were white blood cell profile and gastrointestinal parasite infection based on faecal examination. Data were analysed using One Way ANOVA and presented descriptively. Faecal examination results showed gastrointestinal parasite infection with dominant species Haemonchus contortus (5, TPG 1-33), Trichuris spp. (3, maximum TPG 11), Strongyloides spp. (4, maximum TPG 61), Eimeria spp. (6, mild to severe infection), and Cystotoma spp. (5). Ivermectin administration significantly affected the percentage of neutrophils, eosinophils and basophils (p0.05), indicating that Ivermectin did not affect all white blood cell types equally. In conclusion, this study showed that pea goats were infected with gastrointestinal parasites with a predominance of Haemonchus contortus, Trichuris spp., Strongyloides spp., Eimeria spp. and Cystotoma spp. Ivermectin administration was shown to affect neutrophils, eosinophils and basophils, reflecting the immune response to parasitic infection.